Implementasi Kebijakan Sistem Pembelajaran Daring di Pesantren Persatuan Islam 1-2 Bandung Pada Masa Pandemi Covid-19 - Nurti Budiyanti; Supiana Supiana; Qiqi Yuliati Zakiah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
This study aims to analyze the policy of teaching and learning activities carried out at pesantren Persatuan Islam 1-2 Bandung. This research uses qualitative method, in collecting information and data on the use of observation techniques and interviews online. The results of the research found that the implementation of the policy of teaching and learning activities during the pandemic is enforced two stages, the learning stage turns and the online stage as a whole. In line with the increasing development of covid 19, the Head of Pesantren which is often referred to as Mudir Am determines the policy of teaching and learning activities using online systems, this system becomes the main choice that is seen as more effective in anticipating the spread of the outbreak.The learning used in this online system uses media such as zoom, google classroom, google meet and whatsapp group. Muhadharah activities and other constructions are diverted based online. This policy is established in order to create security and protection for all stakeholders in pesantrenn environment.